2009
DOI: 10.1007/s00335-009-9211-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic loci involved in diabetes using a rat model of depression

Abstract: While diabetic patients often present with comorbid depression, the underlying mechanisms linking diabetes and depression are unknown. The Wistar Kyoto (WKY) rat is a well-known animal model of depression and stress hyper-reactivity. In addition, the WKY rat is glucose intolerant and likely harbors diabetes susceptibility alleles. We conducted a quantitative trait loci (QTL) analysis in the segregating F2 population of a WKY × Fischer 344 (F344) inter-cross. We have previously published QTL analyses for depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Moreover, in some quantitative trait loci (QTL) studies, HPA axis measures and metabolic traits shared common genetic influences. For instance, glucose dysregulation‐related loci overlapped with HPA axis‐related loci on chromosomes 3, 5, and 7 in a F2 WKYxF344 rat intercross 66 . Other QTL studies also suggest the involvement of candidate genes related to corticotropic function in metabolic traits in humans, pigs, or rodents 67 .…”
Section: Functional Consequences Of Genetic Variationmentioning
confidence: 97%
“…Moreover, in some quantitative trait loci (QTL) studies, HPA axis measures and metabolic traits shared common genetic influences. For instance, glucose dysregulation‐related loci overlapped with HPA axis‐related loci on chromosomes 3, 5, and 7 in a F2 WKYxF344 rat intercross 66 . Other QTL studies also suggest the involvement of candidate genes related to corticotropic function in metabolic traits in humans, pigs, or rodents 67 .…”
Section: Functional Consequences Of Genetic Variationmentioning
confidence: 97%
“…As is the case in uncontrolled or poorly controlled diabetes , the high circulating levels of corticosterone in the STZ rats indicate enhanced HPA axis activity. The mechanisms responsible for this abnormality are unclear.…”
Section: Discussionmentioning
confidence: 87%
“…These data support many previous findings from an LH x LN F2 intercross where 23 quantitative trait involving body weight, blood pressure, and plasma lipids mapped to the same chromosome [ 18 , 19 ]. Genetic studies in other rat strains have also identified loci for hypertension and other MetS traits on rat chromosome 17 [ 27 33 ]. Previously a consomic rat having a BN chromosome 17 on an LH genome background was generated [ 20 ].…”
Section: Discussionmentioning
confidence: 99%